Volume 4: Heat Transfer, Parts a and B 2008
DOI: 10.1115/gt2008-50892
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leading Edge Diameter on the Horse Shoe Vortex and Endwall Heat Transfer

Abstract: The endwall of the first stage vane / blade of modern high temperature gas turbine has been exposed to severe heat transfer environments. Due to the formation of a horse shoe vortex (HV), the flow field of a vane and blade leading edge juncture to endwall is especially complicated and it is difficult to estimate the heat transfer coefficients and the film cooling effectiveness levels in this area. This paper describes the results of experimental and numerical studies on the heat transfer and flow dynamics in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…The time-mean velocity is typical of other studies, with a large primary vortex that is elliptical-shaped. These results do not indicate strong secondary or tertiary vortices upstream of the primary vortex, as found by some researchers [2,15], although those vortices are also not apparent in the Rood wing results of Devenport and Simpson [4]. The time-mean turbulent kinetic energy is also typical of other studies, with high turbulence in the core of the vortex.…”
Section: A Time Mean Velocity Measurementssupporting
confidence: 44%
See 2 more Smart Citations
“…The time-mean velocity is typical of other studies, with a large primary vortex that is elliptical-shaped. These results do not indicate strong secondary or tertiary vortices upstream of the primary vortex, as found by some researchers [2,15], although those vortices are also not apparent in the Rood wing results of Devenport and Simpson [4]. The time-mean turbulent kinetic energy is also typical of other studies, with high turbulence in the core of the vortex.…”
Section: A Time Mean Velocity Measurementssupporting
confidence: 44%
“…Unsteady heat flux measurements upstream of the Rood wing by Lewis et al [5] did not exhibit any bimodal behavior in PDF's in the junction flow region, despite the bimodal flow behavior seen by Devenport and Simpson [4]. Hada et al [15] replicated the "double-band" heat transfer phenomenon in their study of a wide range of inlet velocities, boundary layer thicknesses, and body thicknesses. They also reported that as the body thickness decreased, the endwall heat transfer increased proportionally.…”
Section: Previous Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Praisner and Smith [1] and Hada et al [11] complemented time mean flowfield measurements with time mean heat transfer measurements to help explain the convective heat transfer at the junction. They found a primary high heat transfer band very close to the junction, which follows the leading edge contour, and a further upstream secondary high heat transfer band linked to the secondary vortex upstream of the large primary vortex.…”
Section: Previous Studiesmentioning
confidence: 99%
“…They found a primary high heat transfer band very close to the junction, which follows the leading edge contour, and a further upstream secondary high heat transfer band linked to the secondary vortex upstream of the large primary vortex. Hada et al [11] also examined the effects of varying boundary layer thickness, body thickness of the bluff body, and incoming Reynolds number on the surface Stanton number and found that the double bands of high wall heat transfer persisted in all those instances. Swisher et al [14] investigated the unsteadiness in heat flux along the stagnation streamline in front of a streamlined cylinder using a high-frequency-response heat flux microsensor (HFM) and found an increase in the RMS of heat flux unsteadiness as much as 30% over the mean heat flux in the vortex core.…”
Section: Previous Studiesmentioning
confidence: 99%